1987
DOI: 10.1016/0012-821x(87)90201-9
|View full text |Cite
|
Sign up to set email alerts
|

15N/14N variations in Cretaceous Atlantic sedimentary sequences: implication for past changes in marine nitrogen biogeochemistry

Abstract: At two locations in the Atlantic Ocean (DSDP Sites 367 and 530) early to middle Cretaceous organic-carbon-rich beds ("black shales") were found to have significantly lower 815N values (lower 15N/14N ratios) than adjacent organic-carbon-poor beds (white limestones or green claystones). While these lithologies are of marine origin, the black strata in particular have 815N values that are significantly lower than those previously found in the marine sediment record and most contemporary marine nitrogen pools. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
84
1

Year Published

1993
1993
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(91 citation statements)
references
References 35 publications
6
84
1
Order By: Relevance
“…Coupling with abundant geohopanoids, derivatives of components of cellular membrane of prokaryotes, in these samples, they concluded the diazotrophic cyanobacteria could have been major primary producers during the OAE2. The δ bulk values in the Cretaceous black shales were also reported by Rau et al (1987). They determined the δ bulk of the black shales (they referred them "laminated black marlstone" and "black clay stone") from DSDP sites 367, 530, and 603 in Atlantic Ocean and found that the δ bulk values are in a range from -2.7 to +0.6‰, whereas those of adjacent organic-poor rock samples were substantially higher than those (-0.7 to +5.7‰).…”
Section: Nitrogen Isotopic Composition Of Bulk Sediments Insupporting
confidence: 64%
“…Coupling with abundant geohopanoids, derivatives of components of cellular membrane of prokaryotes, in these samples, they concluded the diazotrophic cyanobacteria could have been major primary producers during the OAE2. The δ bulk values in the Cretaceous black shales were also reported by Rau et al (1987). They determined the δ bulk of the black shales (they referred them "laminated black marlstone" and "black clay stone") from DSDP sites 367, 530, and 603 in Atlantic Ocean and found that the δ bulk values are in a range from -2.7 to +0.6‰, whereas those of adjacent organic-poor rock samples were substantially higher than those (-0.7 to +5.7‰).…”
Section: Nitrogen Isotopic Composition Of Bulk Sediments Insupporting
confidence: 64%
“…This hypothesis is supported by the canonical view that the final step in the oxygenation of Earth"s surface occurred in the Neoproterozoic (Section 2.1) and that therefore the Phanerozoic ocean was fully oxygenated with only brief interruptions during anoxic events that favored a temporary return to anaerobic nitrogen cycling (e.g. Junium and Arthur, 2007;Ohkouchi et al, 2006;Rau et al, 1987;Schoepfer et al, 2012;Sephton et al, 2002). However, it is possible that the redox state of the ocean was not stable in the early Phanerozoic, and this may have significantly affected nitrogen cycling.…”
Section: Phanerozoic (Since ~05 Gyr)mentioning
confidence: 88%
“… 15 N org values of type II kerogens (Fig. 4a) are typical for black shales where  15 N is usually between -3 and +2‰ (e.g., Rau et al, 1987;Dumitrescu and Brassell, 2006;Meyers, 2006 Boudou et al, 1984a;Burchill and Welch, 1989;Whiticar, 1996;Ader et al, 1998a;Rimmer et al, 2006). …”
Section: Elemental Rank and Isotopic Characterizationmentioning
confidence: 98%